Magnetic Order in NbS Nanoribbons - Güller, Francisco (2013)
Transition metal dichalcogenides are well known for their laminar structure, similar to that of graphite. The bulk structure of many of them has been the subject of several studies during the last 30 years, due to their many potential technological applications. In the year 2004, Novoselov achieved to isolate not only graphene but layers of other bidimensional crystals as well, among them some dichalcogenides . Several metallic dichalcogenides exhibit strong Fermi surface nesting and charge density wave phases. In this contribution we study the magnetic order in NbS2 nanoribbons, a metallic dichalcogenide, via ab initio calculations. We investigate the magnetization of the systems for several initial spin configurations as a function of ribbon width, comparing with results obtained for ribbons of a non metallic dichalcogenide, MoS2. Atoms in the NbS2 ribbons show a wave-like pattern in their magnetic moments, going from one edge to the other. The physical origin of this magnetic behavior is discussed.